“I find that the course has surely supported me [in my teaching]”. The Relationship between Theory and Praxis in the Field - Jónsdóttir, Lilja M.; Pálsdóttir, Guðbjörg; Hauksdóttir, Edda Kristín (Menntavísindasvið Háskóla Íslands, 2021)
Teacher education has developed rapidly over the recent decades. The structure of teacher education in Iceland has undergone frequent changes and it is therefore relevant to look more closely at how and why some of these changes have been implemented. In structuring teacher education it is important to account for the fact that teachers’ professionalism is based on both professional and personal aspects. Teacher education must, therefore, include subject studies, general pedagogy as well as pedagogical content knowledge and field studies. In that way it is possible to help student teachers connect theory and practice, and use that foundation to create opportunities for successful professional development. In the school year 2019–2020, student teachers were for the first time offered a whole-year field study, in the form of a paid internship, as part of a teacher education program at the University of Iceland, School of Education. This field work is part of the whole-year course Teaching and Learning – Becoming a Professional I and II, a total of 35 credits (ECTs), of which the field study accounts for 24 credits. This course is placed in the final year at master’s level, replacing two master’s courses: Teaching and Learning – Becoming a Professional (25 credits) and Subject Teaching (10 credits). The central aim of the course is to strengthen the connection between theory in the teacher education program and praxis in the field. Campus-based teaching takes place weekly, where the diverse aspects of teaching and pedagogy are introduced and discussed in small groups. The student teachers then explore these aspects in the field, test them in their own teaching and discuss the various issues and incidents that might occur with their mentor teacher. Alongside this process, the student teachers have to reflect critically on their practice and keep a journal in which they record their experiences during the course of the year. Through formative assessment the student teachers become increasingly able to critically ...